The Effect of Teaching Technologies Education by ALEN HOVER Model of Students College Basic Education for learn Skills for Creative Thinking (Journal of the College of Basic Education, 2022)
in order to check the aim of the research putting the two following hypotheses :- There was no statistically significant difference (0.05) between the average scores of the experimental group of students who studied according to ALEN HOVER Model and the average score of the students of the control group who studied according to the usual method in the creative thinking test. The researcher uses a partially controlled experimental design, which have Creative Thinking, The experiment was applied on the Basic Education Students The Department of Islamic Education was selected from the basic education departments, The number of its members (52) students They are divided into two study rooms. In order to verity null hyopththsis The creative thinking test, which consisted of (8) They were confirmed by the use of the Kjoder-Richardson-20 for the achievement test and the creative thinking test and the stability coefficient respectively. The achieve ment of experimental group who were taught by ALEN HOVER Model is more than that of the control who were taught by the tradition method in the Creative Thinking . The value of counting (t) was (2,67) while the tableted (t) was (2,000) at the level of significance (0,05) . From these results researcher concluded that teaching by ALEN HOVER an effect on student Creative Thinking in Technologies Education as the volume effect (0.07). In the light of that, the researcher has set a number of recommend and a tines and suqqestion conserving the results of the study.